Preparation of nanoparticulate DyMnO3 microwave-assisted method and its photocatalytic activity. (4th July 2019) - Yang, Jiani; Xie, Xinyu; Tang, Peisong; Chen, Haifeng; Lv, Chunyan
Abstract: In this article, using dysprosium oxide, nitric acid, citric acid and manganese acetate as the raw materials, the precursor of DyMnO3 was obtained by microwave-assisted method. And the DyMnO3 sample was prepared at 650 °C to 950 °C. DyMnO3 samples were characterized by thermogravimetric and differential scanning calorimetry (TG-DSC), X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR). The photocatalytic activity of DyMnO3 samples was studied with methyl orange solution as the simulated sewage. The results show that the pure DyMnO3 can be obtained through calcination at 750 °C, and the DyMnO3 have an average particle size of 80–100 nm. The results show that the degradation rate of methyl orange is nearly 85% and the photocatalytic activity is the best when the DyMnO3 samples are calcined at 750 °C after UV irradiation at 120 min. The purity of DyMnO3 sample is the highest when the calcination temperature is 750 °C, and its crystal shape is complete, the particle size is uniform and the dispersion is better.